ANALYSIS OF SIGNAL QUALITY ON MOBILE DEVICES - Cristina Bach, Rute; Fernandes, Sula; Alex Alves de Marchi, Vitor (Journal of Interdisciplinary Debates, 2024)
The objective of this work is to measure the signal strength of mobile telephony to verify the signal quality of two mobile operators in the urban area of ​​the municipality of Santa Helena / PR. Signal strength data is obtained through a smartphone application, measured at different points in the municipality. The results obtained according to the statistical calculations performed show that for X operator the signal quality is between good and excellent, for Y, the signal quality is between regular and poor.